2020
DOI: 10.1080/13670050.2020.1840508
|View full text |Cite
|
Sign up to set email alerts
|

Business English students’ multifaceted and contradictory perceptions of intercultural communication education (ICE) at a Chinese University

Abstract: Intercultural communication education (ICE) is occurring in different departments and faculties of higher education globally. Yet, there is a lack of research on how this complex field is perceived by both teachers and students. The same goes for the perceptions of the ideal teacher of the subject. This article proposes to fill these gaps by problematizing current discussions about ICE. First, the article presents an overview of the field and shows how polysemic, ideologically and politically oriented ICE is. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The more sensitive and aware they become of their own intercultural experience, the more they could be ready to accept that the "others" are more complex than assumed. In this sense, renewed interculturality aims to prepare students for the flexible and ever-changing nature of intercultural encounters (Simpson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more sensitive and aware they become of their own intercultural experience, the more they could be ready to accept that the "others" are more complex than assumed. In this sense, renewed interculturality aims to prepare students for the flexible and ever-changing nature of intercultural encounters (Simpson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we concluded that an interpersonal and practical assignment based on renewed interculturality contributed to translator students' intercultural competence in several aspects: gaining self-confidence, reducing the anxiety stemming from cultural differences, improving their intercultural sensitivity and mindfulness, noticing cultural stereotypes, and reflecting on cultural differences, as well as commonalities. As Simpson et al (2022) put it, renewed and performative interculturality has the potential to break down the borders between similarity and difference, by taking both into account in examining intercultural encounters.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large amount of research demonstrating students' perceptions of various English language courses, language skills abilities, teaching methods or evaluations of the teaching reality experience in general (Kung and Chuo, 2002;Sung and Yeh, 2012;AbuSa'aleek, 2015;Jiménez, 2018;Romadhon, Hikmah and Hellystia, 2018;Kamugisha, 2021). As it can be seen in the resources, the biggest country that acknowledges the importance of business-related knowledge and launches BE undergraduate programs in universities is China, which is additionally highly perceptive of introducing specialized programs as part of the BE programs goals, such as intercultural communication education (Guiyu and Yang, 2016;Simpson, Dervin and Tao, 2022). Recently, there has been a range of specialized studies that have examined students' perceptions of the following: English language needs (Ghenghes, Hamed and Abdelffath, 2011), BE curriculum setting including students' expectations and satisfaction with BE courses (Zhengguo and Wenzbong, 2016), teaching strategies and BE materials implemented in classes (Abduh and Sofyan, 2019), the influence of language skills on academic, professional and personal development (Hariharasudan, Nawaz and Panakaje, 2021), blog-based BE vocabulary acquisition (Ching, 2011), BE writing ability (Wand and Shen, 2019).…”
Section: Justification Of the Studymentioning
confidence: 99%
“…As an emerging independent research field, business discourse research extends its influence across many other interdisciplinary applications in extensive research. It is apparent that #4 higher education and #7 knowledge are related to pedagogical research, including but not limited to intercultural/cross-cultural communication education (Simpson et al, 2022;Zhang et al, 2022), workplace communication (Chan, 2019), technology-enhanced communication (Zhao et al, 2022), and leadership communication (Doshi et al, 2021). These studies reveal the application of business discourse in higher education and the construction of knowledge systems that have practical significance for cultivating students in the digital era.…”
Section: Other Applications and Extensive Research (#4 #7 #8)mentioning
confidence: 99%